ChM. Dr Wan Norfazilah develops LabQuest, innovative board game to enhance students’ understanding of ISO standards - Nur Hartini, Mohd Hatta (UMPSA, 2025)
GAMBANG, 20 June 2025 – A group of researchers from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), led by a Senior Lecturer from the Faculty of Industrial Sciences and Technology (FSTI), ChM. Dr Wan Norfazilah Wan Ismail, has successfully developed LabQuest, an innovative board game that adapts the principles of ISO 9001:2015 and ISO/IEC 17025:2017 standards in the form of a real laboratory management simulation.